2018
DOI: 10.1038/s41598-018-22396-5
|View full text |Cite
|
Sign up to set email alerts
|

The early effects of external and internal strategies on working memory updating training

Abstract: The mechanisms underlying working memory training remain unclear, but one possibility is that the typically limited transfer effects of this training reflect adoption of successful task-specific strategies. Our pre-registered randomized controlled trial (N = 116) studied the early effects of externally given vs. internally generated strategies in an updating task (n-back) over a 5-day period with a single 30-minute training session. Three groups were employed: n-back training with strategy instruction (n = 40)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
94
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(109 citation statements)
references
References 28 publications
10
94
2
3
Order By: Relevance
“…Furthermore, the level of detail and type of self-generated N-back strategies reported by the uninstructed participants was significantly related to their post-test N-back performance. The results in Laine et al (2018) provided strong evidence for the Strategy Mediation Hypothesis, according to which strategy changes rather than increased WM capacity may underlie successful WM training outcomes ( Dunning & Holmes, 2014 ; Soveri et al, 2017 ).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, the level of detail and type of self-generated N-back strategies reported by the uninstructed participants was significantly related to their post-test N-back performance. The results in Laine et al (2018) provided strong evidence for the Strategy Mediation Hypothesis, according to which strategy changes rather than increased WM capacity may underlie successful WM training outcomes ( Dunning & Holmes, 2014 ; Soveri et al, 2017 ).…”
mentioning
confidence: 77%
“… Laine et al (2018) proposed and explicitly tested one aspect of this, the Strategy Mediation Hypothesis of WM training: that task-specific near-transfer gains are driven by developing and using a task-specific strategy during training. In younger adults, they used the N-back training paradigm ( Kirchner, 1958 ) in which participants see an ongoing string of individual stimuli (e.g., digits) stream on a computer screen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For a power of 80%, a sample size of 40 is required to detect a large effect ( f =0.40) and a sample size of 98 for a medium effect ( f =0.25). Three previous cognitive training randomised controlled trials have reported medium to large effect sizes (eta-squared range 0.15–0.2744). Therefore, assuming an allocation ratio of 1:1, a sample between 40 and 98 participants should be sufficient to achieve adequate statistical power.…”
Section: Methods and Analysismentioning
confidence: 96%
“…We asked -what is it that participants learn which enables their substantial improvement in a challenging updating task designed to require limited-capacity online manipulations? The few recent studies that addressed this question suggest that the use of a task-specific strategy may facilitate training-induced improvement (Fellman et al, 2020;Laine, Fellman, Waris, & Nyman, 2018;Linares et al, 2019;. Indeed, the need for a strategy that reduces WM requirements has been gradually acknowledged (Redick, 2019).…”
Section: Introductionmentioning
confidence: 99%